1974
DOI: 10.1159/000152632
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Blood Markers and Anthropometry of the Populations in Aswan Governorate, Egypt

Abstract: Populations of Aswan governorate in Egypt have been studied with respect to blood, serum and enzyme groups as well as some other anthropological characters. One hemoglobin variant (Hb Khartoum) was detected in the Nubians. The ABO gene frequencies were: r = 0.66, p = 0.18 and q = 0.14 in Aswanese; r = 0.67, p = 0.22 and q = 0.10 in Nubians; RhD factor was positive in all Aswanese and Bisharins and negative in 1.4% of the Nubians; G-6-PD deficiency was 1.4% in Aswan city, 2% in Nubia and absent in Bisharins; Gd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…The gene frequencies for the G6PD, AP, and Hp polymorphisms are in agreement with those reported for a Nubian population by A z im , et al [2], In this study, no attempt was made to distinguish the G6PD deficiency pheno type, and types were assigned on the basis of electrophoretic mobility only. The absence or more properly the very low frequency of the APC allele is confirmed in this study, but the APR allele seen in 4 of 62 individuals by A zim et al [2] was not observed in this study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The gene frequencies for the G6PD, AP, and Hp polymorphisms are in agreement with those reported for a Nubian population by A z im , et al [2], In this study, no attempt was made to distinguish the G6PD deficiency pheno type, and types were assigned on the basis of electrophoretic mobility only. The absence or more properly the very low frequency of the APC allele is confirmed in this study, but the APR allele seen in 4 of 62 individuals by A zim et al [2] was not observed in this study.…”
Section: Resultssupporting
confidence: 92%
“…The absence or more properly the very low frequency of the APC allele is confirmed in this study, but the APR allele seen in 4 of 62 individuals by A zim et al [2] was not observed in this study. The APC allele has been reported to be present in presumably non-Nubian Egyptians [8] who have a significantly higher A P a gene frequency.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The frequency of G6PD deficiency we report here for Egyptians, Irianians, and Lebanese are in general agreement with previous reports [13, 14, 15, 16](table 4). However, we obtained a frequency of 3.6% for Jordanians.…”
Section: Discussionsupporting
confidence: 93%
“…This frequency is, however, lower than the previously reported values of 0–2% for Egypt [13, 14], 1.7% for Jordan [17], and 3.09% for Lebanon [23]. An earlier study carried out in Kuwait in 1966 in 118 samples, using the field screening method (the methaemoglobin reduction test), reported a deficiency rate of 18.9% for the entire population [24].…”
Section: Discussionmentioning
confidence: 64%